A New Algorithm for Solving Large-Scale Generalized Eigenvalue Problem Based on Projection Methods. (14th December 2020) - Nedamani, F. Abbasi; Sheikhani, A. H. Refahi; Najafi, H. Saberi
Abstract : In this paper, we consider four methods for determining certain eigenvalues and corresponding eigenvectors of large-scale generalized eigenvalue problems which are located in a certain region. In these methods, a small pencil that contains only the desired eigenvalue is derived using moments that have obtained via numerical integration. Our purpose is to improve the numerical stability of the moment-based method and compare its stability with three other methods. Numerical examples show that the block version of the moment-based (SS) method with the Rayleigh–Ritz procedure has higher numerical stability than respect to other methods.